Perbedaan Pengunaan Kateter Intermitten dan Kateter Indweling Terhadap Terjadinya Infeksi Saluran Kemih - prasetyo, dandy alghifary; supono, supono; asjaswarni, tri (Poltekkes Kemenkes Malang, 2023)
Urinary tract infection is an infectious disease that often occurs in health services throughout the world. Urinary tract infection is ac ondition of the presence of microorganisms in the urinary tract with the presence of bacterial colonies. The incidence of urinary tract infections occurs because the catheter has symptoms and is caused by prolonged catheterization. The purpose of this literature review study was to determine the use of long and short-term catheters in the incidence of urinary tract infections from the selected articles. This writing uses the literature review method with the library sources used are articles from 2011-2021 through a search process in pubmed, sciencedirect, and scholar with the search results obtained 10 articles that are ready to be analyze dusing JBI Critical Appraisaltools. Articles are taken from reputable or accredited databases. The results of a review of 10 journals showed the incidence of urinary tract infections related to the use of indwelling catheters (4articles), using temporary catheters could reduce the incidence of urinary tract infections (3articles) and based on age and using permanent and temporary catheters experiencing UTI (3 articles). Based on the results of a literature review from 10 journals, it was found that there were differences in the use of intermittent catheters and indwelling catheters for the occurrence of urinary tract infections, where the incidence of infection was more risky if using an indwelling catheter that was used for more than 3 days of use.